Readability Level of the First Intermediatee Grade from the Point of of View of Female Teachers in the Kingdom of Saudi Arabia - Al-Subaie, Nowayer Mohammed (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to identify the level of readability of the science book of the first intermediatee grade from female teachers' point of view, and to reveal the presence of statistically significant differences between the female teachers’ points of view in readability level of the scientific texts in the science book of the first intermediatee grade according to two variables of specialization (Chemistry, Biology and Physics) and years of experience.To achieve the objectives of the study, the descriptive survey method was used. A questionnaire consisting of (30) phrases distributed over (5) axes was used as a tool for the study. It was distributed to a randomly selected sample consisting of (120) science teachers of intermediate grade in Taif.The results of the study showed that the level of readability of the science book of the first intermediatee grade from the female teachers’ point of view was large, with an arithmetic mean (3,56). It also showed that there were no statistically significant differences between the female teachers’ points of view in the level of readability of the science book of the first intermediatee grade according to the variables of specialization and years of experience.
Keywords: Degree of readability; science book; the first intermediatee grade